Research on farmers’ households credit behavior and social capital acquisition - Ping, Li; Xiaosong, Song; Jinzhao, Li (Frontiers in Psychology, 2022)
In order to further investigate and analyze the influence of social capital on farmer households’ credit behavior and its significant positive effect, a method of a scientific measure of farmer households’ social capital was proposed in the research. The method aimed to build the empirical model of farmer households’ credit behavior based on the business performance and social capital influence. Through the regression analysis of the influence of the social capital on the channels of farmer households’ access to credit, it was found that the analysis results of the two-variable probit model showed that the error correlation coefficients of the credit by the formal channel and the informal channel among the three models were 0.153, 0.158 and 0.152 respectively. The significance levels of the correlation coefficients were all more than 1%, indicating that the regression results passed the significance test and were relatively accurate.